2021
DOI: 10.1186/s12890-021-01532-4
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on analgosedation, monitoring, and recovery time for flexible bronchoscopy: a systematic review

Abstract: Background Patients undergoing bronchoscopy in spontaneous breathing are prone to hypoxaemia and hypercapnia. Sedation, airway obstruction, and lung diseases impair respiration and gas exchange. The restitution of normal respiration takes place in the recovery room. Nonetheless, there is no evidence on the necessary observation time. We systematically reviewed current guidelines on bronchoscopy regarding sedation, monitoring and recovery. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…We only recruited patients with ASA I-II and those who had a procedure time <30 min (eg, endobronchial inspection, bronchoscopic biopsy, and bronchoalveolar lavage). However, with the development of respiratory endoscopy technology, more complex endoscopic therapy is required under anesthesia, when there is no contraindication according to guidelines ( Wahidi et al, 2011 ; Strohleit et al, 2021 ; Long et al, 2022 ). A previous study reported that ciprofol produces similar levels of sedation compared with propofol in the intensive care unit setting to achieve required sedation times of 6–24 h ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We only recruited patients with ASA I-II and those who had a procedure time <30 min (eg, endobronchial inspection, bronchoscopic biopsy, and bronchoalveolar lavage). However, with the development of respiratory endoscopy technology, more complex endoscopic therapy is required under anesthesia, when there is no contraindication according to guidelines ( Wahidi et al, 2011 ; Strohleit et al, 2021 ; Long et al, 2022 ). A previous study reported that ciprofol produces similar levels of sedation compared with propofol in the intensive care unit setting to achieve required sedation times of 6–24 h ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical bronchoscopies, more than half of severe complications, including death, are believed to be related to administration of analgesia and sedation ( 50 , 51 ). The critically ill patient with a protected airway has substantially reduced risk for sedation-induced respiratory depression given presence of mechanical ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…Common complications as pneumothorax, hemorrhage, hypoxia, hypoventilation, laryngo-, and bronchospasm can occur in almost all patients undergoing bronchoscopic procedures. Other problems may occur due to the specific procedure and underlying pathophysiology [5 ▪▪ ].…”
Section: General Considerationsmentioning
confidence: 99%